PENGARUH PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI (STUDI DI DINAS PENGENDALIAN PENDUDUK KELUARGA BERENCANA PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN MINAHASA SELATAN) - HARINDA, DEWANGGA DEVID; RORONG, ARIE; PLANGITEN, NOVVA (JURNAL ADMINISTRASI PUBLIK, 2021)
Career development is one of the most important things in the world of work. Career development is the process of implementing career planning. Where career development includes improving the performance of the employees themselves. This study looked at the influence of Career Development on Employee Performance in the Office of Family Planning Population Empowerment of Women and Child Protection of South Minahasa Regency, which consisted of 52 employees at the Office of Family Planning Population Empowerment and Child Protection of South Minahasa Regency. This study uses quantitative research methods because there are two variables of Career Development (X) and Employee Performance (Y) by analyzing the data using simple linear regression. The results obtained are (a) a constant value of 22.180 while the value of b or the regression coefficient is obtained a positive value of 0.145 so that the equation can be written as Y = 22.180 + 0.145X, where it can be concluded that the direction of the Career Development variable (X) on Employee Performance (Y) is positive, and career development has an effect on employee performance. Keywords: Career Development, Employee, Performance.